2016
DOI: 10.1097/yco.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of eating disorders in Africa

Abstract: The epidemiological study of eating disorders in Africa is still in its infancy. Over time in total four studies providing epidemiological data on specific, formally assessed eating disorders were found. No cases of anorexia nervosa were reported in African epidemiological studies, which concurs with the very low prevalence rates of anorexia nervosa in Latin Americans and in African Americans in the USA. With the DSM-5 criteria for anorexia nervosa, some women in the African studies would have fulfilled the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 35 publications
3
43
0
5
Order By: Relevance
“…Moreover, the second meta-analysis also showed the existence of a similar relation between emotional regulation and anorexia [80]. The lack of significant differences between Polish and Japanese women in the level of intensity of Body Dissatisfaction and Drive for Thinness demonstrated in this article can confirm the results of studies conducted by other authors, which indicate a universal and similar intensity of risk factors for the development of eating disorders in countries influenced by Western culture [1,3,8,11,81].…”
Section: Similarities and Differences Between Polish And Japanese Womensupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, the second meta-analysis also showed the existence of a similar relation between emotional regulation and anorexia [80]. The lack of significant differences between Polish and Japanese women in the level of intensity of Body Dissatisfaction and Drive for Thinness demonstrated in this article can confirm the results of studies conducted by other authors, which indicate a universal and similar intensity of risk factors for the development of eating disorders in countries influenced by Western culture [1,3,8,11,81].…”
Section: Similarities and Differences Between Polish And Japanese Womensupporting
confidence: 85%
“…Analysis of the source literature confirms the continual increase of the number of people suffering from eating disorders worldwide [1,2]. Epidemiological data confirm the increasing importance of the problem in European countries [3,4], including Poland [5,6], the United States of America [7], Latin America [8], Arab countries [9,10], Africa [11], and Asia [12][13][14][15][16], with the risk of development of eating disorders being especially high in Japan [17]. The Global Burden of Disease (GBD) study from 2015 [18] confirmed the steady increase of eating disorders in women all around the world [19].…”
Section: Epidemiology Of Eating Disordersmentioning
confidence: 70%
“…This is in line with warnings that ED such as AN exist in SSA (as seen in case studies) and their relevance in this context should not be underestimated . Point prevalence of BN in young African women has been estimated to be 0.87%, which is within the range reported for young women in HIC and Latin America . The diagnosis of BED is acknowledged as a distinct eating disorder for the first time in DSM‐5 and we are unaware of any estimates of BED in SSA.…”
Section: Introductionsupporting
confidence: 74%
“…That the effect carries over to the children of immigrant families suggests that sociocultural factors likely contribute to the decreased risk. Such factors could include greater acceptance of larger body sizes or social support within the immigrant communities . Our results suggest that assimilation to the receiving countries increases the risk for eating disorders so that it starts approaching that of the native populations.…”
Section: Discussionmentioning
confidence: 73%
“…They are no longer considered to be limited to Western culture, but are tied to economic development, urbanization, and industrialization . Despite reports of rising incidences particularly in Asia , eating disorders still appear rare in many low‐ and middle‐income countries . As the majority of immigration to Denmark and Sweden was from less developed countries, a low base rate of eating disorders in the countries of origin is one plausible explanation for the low rates among immigrants.…”
Section: Discussionmentioning
confidence: 99%